Analysis of Schools and Thoughts in Modern Philosophy (17th-20th Century) - Deni Fadis Zaelani; Siti Fatimah Zahra (Annujum: Journal of Humaniora and Law, 2025)
Philosophy is a general science because it focuses on the Effects or Consequences, and Appearances obtained by rationalizing knowledge from its causes. Modern philosophy is marked by the birth of major schools of thought such as Rationalism, Empiricism, Idealism, Materialism, Positivism, Phenomenology, Existentialism, and Pragmatism. The emergence of this modern philosophy occurred in the 17th century to the early 20th century in Western Europe and North America. The purpose of this study is to determine the schools and thoughts in modern philosophy (17th-20th centuries AD). The research is in the form of Library Research. The results of this study are that modern philosophy is a division in the history of Western Philosophy which marks the end of the era of scholasticism. The time of the emergence of modern philosophy was the 17th century to the early 20th century in Western Europe and North America.